Product Similarity, Benchmarking, and Corporate Fraud - Boone, Audra; Grieser, William; Li, Rachel; Venkat, Parth (Journal of Financial and Quantitative Analysis, 2025)
Abstract We document that firms with greater product similarity to their peers exhibit lower rates of financial fraud. We show that peer similarity is associated with better information environments, which is consistent with monitors’ enhanced ability to benchmark against other firms. The negative relation between product similarity and fraud remains after controlling for alternative mechanisms including incentive compensation structures, competition, and internal and external governance characteristics. Overall, our findings suggest that greater peer similarity increases the marginal cost of fraud, and therefore, ex ante disincentivizing managers from committing fraud.